2007
DOI: 10.1128/jcm.02553-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Results of Detection of Rhinovirus by PCR and Viral Culture in Human Nasal Wash Specimens from Subjects with and without Clinical Symptoms of Respiratory Illness

Abstract: Human rhinoviruses (HRV) cause acute upper respiratory illness. The frequency of HRV-associated illnesses appears greater when PCR assays are used to detect rhinoviruses. The present study performed PCR-based detection of HRV upon entry of subjects into respiratory syncytial virus and parainfluenza type 3 vaccine trials when subjects were symptom-free and upon subsequent development of clinical symptoms of respiratory illness during the trial. The background of HRV PCR positivity in symptom-free individuals (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 29 publications
4
58
2
1
Order By: Relevance
“…Moreover, despite our efforts to design an HRV-specific assay, some HEVs present at high titers in the respiratory specimen could be misidentified as HRV. In addition to these technical issues, the potential for long-term shedding of HRVs in some populations (20,23,28,51) and the high rates of asymptomatic HRV infection found in some studies (11,39,51) make it more difficult to establish an etiologic link to disease. By restricting the testing to HRVs alone, other members of the Picornaviridae that have been implicated in acute respiratory disease would not be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, despite our efforts to design an HRV-specific assay, some HEVs present at high titers in the respiratory specimen could be misidentified as HRV. In addition to these technical issues, the potential for long-term shedding of HRVs in some populations (20,23,28,51) and the high rates of asymptomatic HRV infection found in some studies (11,39,51) make it more difficult to establish an etiologic link to disease. By restricting the testing to HRVs alone, other members of the Picornaviridae that have been implicated in acute respiratory disease would not be identified.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, real-time RT-PCR assays have been described for HRVs/HEVs (8,9,25,38,44) that offer potentially rapid, sensitive, and quantitative results and that are less prone to amplicon contamination. However, because of the more extensive genetic variability of the HRVs and the lack of available sequence data in the public domain, few real-time RT-PCR assays have been described specifically for the HRVs (8,9,44,51), and none to our knowledge has been shown to successfully detect all recognized HRV prototype strains. In this study, we sequenced a portion of the 5ЈNCR of all HRV prototype strains as well as multiple recently circulating field isolates and used these data to develop and evaluate an HRV real-time RT-PCR assay.…”
mentioning
confidence: 99%
“…In contrast, the picornaviruses, EnVs and RhVs, were seen in 31% and 17%, respectively, of tissues tested. We and others have recently demonstrated that RhVs from well children and adults are frequently identified by PCR (12,20). The high frequency of EnVs was unexpected, as they are most commonly associated with enteric disease.…”
mentioning
confidence: 88%
“…Furthermore, it is well known that the presence of a virus in the nasopharynx of a patient with pulmonary disease does not necessarily signify that it is the cause of the disease because it may simply indicate a coincidental upper airways infection, a carrier state, or prolonged shedding of a pathogen that caused a previous infection (9). This may be particularly important in the case of HRV because a number of epidemiological studies have shown that it can be found in the respiratory secretions of 12-22z of asymptomatic subjects (10,11).…”
Section: Gov)mentioning
confidence: 99%